Default and control network connectivity dynamics track the stream of affect at multiple timescales. Issue 5 (22nd October 2021) - Lettieri, Giada; Handjaras, Giacomo; Setti, Francesca; Cappello, Elisa Morgana; Bruno, Valentina; Diano, Matteo; Leo, Andrea; Ricciardi, Emiliano; Pietrini, Pietro; Cecchetti, Luca
Abstract: In everyday life, the stream of affect results from the interaction between past experiences, expectations and the unfolding of events. How the brain represents the relationship between time and affect has been hardly explored, as it requires modeling the complexity of everyday life in the laboratory setting. Movies condense into hours a multitude of emotional responses, synchronized across subjects and characterized by temporal dynamics alike real-world experiences. Here, we use time-varying intersubject brain synchronization and real-time behavioral reports to test whether connectivity dynamics track changes in affect during movie watching. The results show that polarity and intensity of experiences relate to the connectivity of the default mode and control networks and converge in the right temporoparietal cortex. We validate these results in two experiments including four independent samples, two movies and alternative analysis workflows. Finally, we reveal chronotopic connectivity maps within the temporoparietal and prefrontal cortex, where adjacent areas preferentially encode affect at specific timescales.